BUZANO’S INEQUALITY IN ALGEBRAIC PROBABILITY SPACES (2019)
We obtain a generalization of Buzano’s inequality of vectors in Hilbert spaces , using the theory of algebraic probability spaces. In particular, we extend a result of Dragomir given in [7]. Applications for numerical inequalities for n- tuples of bounded linear operators and functions of operators defined by double power series are also generalized.